Photosynthetic Physiology of Blue, Green, and Red Light: Light Intensity Effects and Underlying Mechanisms - Liu, Jun; van Iersel, Marc W. (Frontiers in Plant Science, 2021)
Red and blue light are traditionally believed to have a higher quantum yield of CO2 assimilation (QY, moles of CO2 assimilated per mole of photons) than green light, because green light is absorbed less efficiently. However, because of its lower absorptance, green light can penetrate deeper and excite chlorophyll deeper in leaves. We hypothesized that, at high photosynthetic photon flux density (PPFD), green light may achieve higher QY and net CO2 assimilation rate (An) than red or blue light, because of its more uniform absorption throughtout leaves. To test the interactive effects of PPFD and light spectrum on photosynthesis, we measured leaf An of 'Green Tower' lettuce (Lactuca sativa) under red, blue, and green light, and combinations of those at PPFDs from 30 to 1300 µmol·m-2·s-1. The electron transport rates (J) and the maximum Rubisco carboxylation rate (Vc,max) at low (200 µmol·m-2·s-1) and high PPFD (1000 µmol·m-2·s-1) were estimated from photosynthetic CO2 response curves. Both QYm,inc (maximum QY on incident PPFD basis) and J at low PPFD were higher under red light than under blue and green light. Factoring in light absorption, QYm,abs (the maximum QY on absorbed PPFD basis) under green and red light were both higher than under blue light, indicating that the low QYm,inc under green light was due to lower absorptance, while absorbed blue photons were used inherently least efficiently. At high PPFD, the QYinc [gross CO2 assimilation (Ag)/incident PPFD] and J under red and green light were similar, and higher than under blue light, confirming our hypothesis. Vc,max may not limit photosynthesis at a PPFD of 200 µmol·m-2·s-1 and was largely unaffected by light spectrum at 1000 µmol·m-2·s-1. Ag and J under different spectra were positively correlated, suggesting that the interactive effect between light spectrum and PPFD on photosynthesis was due to effects on J. No interaction between the three colors of light was detected. In summary, at low PPFD, green light had the lowest photosynthetic efficiency because of its low absorptance. Contrary, at high PPFD, QYinc under green light was among the highest, likely resulting from more uniform distribution of green light in leaves.